Effect of Intercropping of Solanum nigrum L., Tomato and Eggplant on Potassium Content under Cadmium Stress. Issue 4 (February 2019) - Li, Rulong; Sun, Guochao; Tang, Yi
Abstract: A pot experiment was conducted to study the effect of intercropping S. nigrum, tomato and eggplant on the potassium content under cadmium stress. The results showed that compared with the control, the intercropping of S. nigrum and tomato has reduced potassium content in S. nigrum stems, leaves and aerial parts by 9.19%, 16.10% and 14.44%, and the content of potassium in tomato roots, stems, leaves and aerial parts was increased by 17.27%, 108.04%, 11.92% and 42.61%, respectively. Compared with the control, the intercropping of S. nigrum and eggplant increased the potassium content of S. nigrum roots, stems, leaves and aerial parts by 5.00%, 2.01%, 8.73% and 3.85%, respectively, and the potassium content of stems, leaves and aerial parts of eggplant decreased by 3.54%, 8.37% and 6.71%. Therefore, the intercropping of S. nigrum and tomato can increase the potassium content of tomato, which is helpful to improve the resistance of tomato to heavy metal.